2001
DOI: 10.1038/modpathol.3880314
|View full text |Cite
|
Sign up to set email alerts
|

Does Exhaustive Search for Microcalcifications Improve Diagnostic Yield in Stereotactic Core Needle Breast Biopsies?

Abstract: Stereotactic core needle biopsy (SCNB) of the breast is a cost-effective alternative to needle localization biopsy for the diagnosis of mammographic calcifications. We questioned whether an exhaustive search for calcium in the small samples obtained in SCNB yields more diagnostic information than that obtained with examination of a standard number of sections. We retrospectively reviewed 168 specimens from 123 patients with mammographic calcifications, including cases in which radiographic suspicion ranged fro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 22 publications
(18 citation statements)
references
References 7 publications
0
18
0
Order By: Relevance
“…43 The presence of birefringent, transparent calcium oxalate crystals should be always excluded before considering apparent calcium loss during histological breast specimen processing. 14,36,44 In Truong's series of 91 cases, calcium oxalate was clinically significant, i.e., actually represented the mammographic calcification, for which the biopsy was performed in 12% of all cases. 45 Calcium oxalate was also found in 31% of cases, even if it did not definitely represent the mammographic calcification for which the biopsy was performed in this study.…”
Section: Polarisable Calcium Oxalate Crystals and False Negative Resultsmentioning
confidence: 98%
See 4 more Smart Citations
“…43 The presence of birefringent, transparent calcium oxalate crystals should be always excluded before considering apparent calcium loss during histological breast specimen processing. 14,36,44 In Truong's series of 91 cases, calcium oxalate was clinically significant, i.e., actually represented the mammographic calcification, for which the biopsy was performed in 12% of all cases. 45 Calcium oxalate was also found in 31% of cases, even if it did not definitely represent the mammographic calcification for which the biopsy was performed in this study.…”
Section: Polarisable Calcium Oxalate Crystals and False Negative Resultsmentioning
confidence: 98%
“…In most of the series studied, false-negative rates for core biopsies sampled for suspicious calcification are low. 14,16,18,37 In Dahlstorm and Jain's series of 125 cases, 18 there were two falseenegative results with a malignant outcome 37 In the series of Lee et al, one of the 106 cases sampled for radiologically suspicious cancer had a malignant outcome two years after the initial biopsy. 38 Bagnall et al found that the presence of five or more flecks of calcium, or three or more cores with calcification, on specimen radiography was associated with 100% sensitivity for diagnosis of malignancy.…”
Section: B3 Category (Lesion Of Uncertain Malignant Potential)mentioning
confidence: 95%
See 3 more Smart Citations